Monitoring and Control System Development on IoT-Based Aeroponic Growth of Pakcoy (Brassica rapa L.) - Renny Eka Putri; Winda Fauzia; Dinah Cherie (Jurnal Keteknikan Pertanian, 2023)
One of the methods that can be used by Indonesian people in urban farming is the Aeroponic method of planting plants. The aeroponic method has a faster nutrient delivery speed than hydroponics and normal plant cultivation. The main objective of this study was to design an aeroponic monitoring and control system for Pakcoy (Brassica rapa. L) using the blynk application as an interface for remote control. The control system used is NodeMCU V3, DHT22 sensor, HC-SR04 ultrasonic sensor and TDS sensor. Plants in the system use a container box measuring 110 cm x 80 cm with 10 nozzles on the inside of the box attached to a ½ inch pipe, with 24 planting holes on the lid of the box with a spacing of 20 cm. The pump will automatically turn on when the temperature in the box is >25oC and will stop when the temperature is =24oC, or when the humidity is <80%. The results obtained during the 30 days of research showed that the average R2 value of the DHT22 sensor was 0.9864 and 0.9864, the HC-SR04 sensor was 0.996 and the TDS sensor was 0.9899. Observations on the growth of pakcoy plants obtained an average height of 13.3 cm for system plants and 13.4 cm for control plants. The average leaf width in system plants was 4.3 cm and 3.6 cm in control plants. the average number of leaves on system plants is 8 leaves and 9 leaves on control plants. The system plant weight was 5.493 gr and that of the control plant was 2.961 gr. The control system that has been made can work well and can be used in aeroponic cultivation of plants.